Twitter monitoring evidence of Covid-19 infodemic in Italy. (30th September 2020) - Calamusa, A; Tardelli, S; Avvenuti, M; Cresci, S; Federigi, I; Tesconi, M; Verani, M; Carducci, A
Abstract: Background: Risk communication is essential for risk management, especially during alarming events, in order to create a balanced risk perception. The tweets follow up can be useful to timely evidence "media storms" or "infodemics" thus suggesting corrective interventions. The spread of Covid-19 has been the occasion to observe the evolution of tweets about this topic, with the aim of evidence peaks of fear Methods: On 30th January 2020 we started a large collection of Italian and English tweets containing the following keywords: "coronavirus", "2019-nCov", "CoronavirusOutbreak", "CoronavirusWho", "WuhanCoronavirus", "coronaviruschina", "coronavirusitalia", "virus cina", "virus cinese", "virus mascherine", "virus paura", "virus polmonite" and "virus vaccine". "Covid-19" and "SARS-CoV-2" were added later. For the data collection Twitter Streaming API was used. Results: The total number of tweets collected till 26th February was approximately 20M, 2M in Italian and 18M in English. The trend of the volume of tweets gathered shows a first small peak between Jan 30th and Feb 1st, but a second, higher, peak is visible after the 21st February, following the report of the Covid-19 clusters in Italy. Italian tweets account for 6% of the first peak and for 22% of the second. The Italian word "paura" firstly appeared on Feb 5th, with a peak after Feb 21th. Conclusions: "infodemics" or "media storms", are situations of uncontrolled diffusion of news and opinion, frequently leading to irrational and counterproductive behaviors. The Italian evolution of tweets indicate since the first day of cluster report, a clear escalation of fear, that suggests timely corrective actions to facilitate the disease control. Key messages: With the twitter monitoring we demonstrate that since 21th February an infodemic is spreading in Italy. The twitter follow up can be used to timely evidence a public alarm, motivate corrective interventions and. evaluate the efficacy of them.